Management of Allergic Rhinitis - Dr. Sangeeta Bhanwra (International Journal of Pharma and Bio Sciences, 2011)
Allergic rhinitis (AR) is an IgE mediated hypersensitivity of the mucous membrane of the nasal airways characterized by nasal symptoms, such as nasal congestion, rhinorrhoea , sneezing and itchy nose.The management of AR consists of allergen avoidance, when possible and the oral and intranasal H1antihistamines,intra-nasal corticosteroids, leukotriene modifiers, mast cell stabilizers and decongestants